Hermeneutika Hadis Gender (Studi Pemikiran Khaled M. Abou El Fadl dalam Buku Speaking in God’s Name; Islamic Law, Authority And Women) - Abdul Majid (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2013)
This paper is aimed to construct the Khaled M. Abou al-Fadl’s hermeneutics on hadiths gender, by examining its authentity and interpretation. This study brings a study case on a number of fatwas of Council for Scientific Research and Legal Opinion, the Saudi Arab-based Fatwa Institute. Abou El- Fadl applies a number of hermeneutic works; such as, negotiating process among texts, authors, the prophet’s traditions, and transmitters, as well as the readers. The hermeneutics work was throuruoghly counducted by bringing together the five principal rules: honesty, deligency, comprehensiveness, rationality, and self-restraint. A number of findings found is as follow: first, hadiths being bases of the fatwa are inadequate. Some of them are not authentic and yet proportionally. Second, hadith is the long final authorship product from the prophet as the first author to the level of hadith collector such as Imam Bukhori. Finally, each author's subjectivity can be tightly attached to the hadiths that he or she revealed which historically must be explored.